Syn-rift unconformities punctuating the lower-middle Cambrian transition in the Atlas Rift, Morocco - Álvaro, J. Javier (2015)
The Cambrian Tamdroust and Bab n’Ali Volcanic Complexes represent two magmatic episodes developed in the latest Ediacaran–Cambrian Atlas Rift of Morocco. Their rifting pulses were accompanied by accumulation of volcanosedimentary edifices (dominated by effusive lava flows in the former and explosive acidic aprons in the latter) associated with active tilting and uplift. Sealing of their peneplaned horst-and-graben palaeotopographies led to the onset of distinct onlapping geometries and angular discordances capping eroded basements ranging from the Ediacaran Ouarzazate Supergroup to the Cambrian Asrir Formation. Previous interpretations of these discordances as pull-apart or compressive events are revised here and reinterpreted in an extensional (rifting) context associated with active volcanism. The record of erosive unconformities, stratigraphic gaps, condensed beds and onlapping patterns across the traditional “lower–middle Cambrian” (or Cambrian Series 2–3) transition of the Atlas Rift must be taken into consideration for global chronostratigraphic correlation based on their trilobite content.